Pharmacokinetics, distribution, and excretion of sodium oligomannate, a recently approved anti-Alzheimer's disease drug in China - Jiaojiao Lu; Qiongqun Pan; Jieqiang Zhou; Yan Weng; Kaili Chen; Lv Shi; Guanxiu Zhu; Chunlin Chen; Liang Li; Meiyu Geng; Zhenqing Zhang (Elsevier, 2022)
The National Medical Products Administration has authorized sodium oligomannate for treating mild-to-moderate Alzheimer's disease. In this study, an LC-MS/MS method was developed and validated to quantitate sodium oligomannate in different biomatrices. The plasma pharmacokinetics, tissue distribution, and excretion of sodium oligomannate in Sprague-Dawley rats and beagle dogs were systematically investigated. Despite its complicated structural composition, the absorption, distribution, metabolism, and excretion profiles of the oligosaccharides in sodium oligomannate of different sizes and terminal derivatives were indiscriminate. Sodium oligomannate mainly crossed the gastrointestinal epithelium through paracellular transport following oral administration, with very low oral bioavailability in rats (0.6%-1.6%) and dogs (4.5%-9.3%). Absorbed sodium oligomannate mainly resided in circulating body fluids in free form with minimal distribution into erythrocytes and major tissues. Sodium oligomannate could penetrate the blood-cerebrospinal fluid (CSF) barrier of rats, showing a constant area under the concentration-time curve ratio (CSF/plasma) of approximately 5%. The cumulative urinary excretion of sodium oligomannate was commensurate with its oral bioavailability, supporting that excretion was predominantly renal, whereas no obvious biliary secretion was observed following a single oral dose to bile duct-cannulated rats. Moreover, only 33.7% (male) and 26.3% (female) of the oral dose were recovered in the rat excreta within 96 h following a single oral administration, suggesting that the intestinal flora may have ingested a portion of unabsorbed sodium oligomannate as a nutrient.